Sol-gel preparation of self-cleaning SiO2-TiO2/SiO2-TiO2 double-layer antireflective coating for solar glass - Wensheng Lin; Jiaxian Zheng; Lianghong Yan; Xinxiang Zhang (Results in Physics, 2018)
Self-cleaning SiO2-TiO2/SiO2-TiO2 double-layer antireflective (AR) coating is prepared by sol-gel process. SiO2 sol is prepared by using tetraethyl orthosilicate (TEOS) as precursor and ammonia as catalyst, while TiO2 sol was prepared by using tetrabutyl orthotitanate (TBOT) as precursor and hydrochloric acid as catalyst. The effect of TiO2 content on refractive index, abrasion-resistance and photo-catalytic activity of SiO2-TiO2 hybrid thin films or powders is systematically investigated. It is found that the refractive index of SiO2-TiO2 hybrid thin films increases gradually from 1.18 to 1.53 as the weight ratio of TiO2 to SiO2 increased from 0 to 1.0. The SiO2-TiO2 hybrid thin film and powder possesses good abrasion-resistance and photo-catalytic activity, respectively, as the weight ratio of TiO2 to SiO2 is 0.4. The degradation degree of Rhodamine B by SiO2-TiO2 hybrid powder is 88.3%. Finally, SiO2-TiO2/SiO2-TiO2 double-layer AR coating with high transmittance, abrasion-resistance and self-cleaning property is realized. Keywords: Sol-gel process, Antireflective coating, Silica, Titania, Self-cleaning